The measurement of microplastics in surface water and their impact on histopathological structures in wading birds of district Lahore - Mehboob, Shaza; Anjum, Khalid Mahmood; Azmat, Hamda; Imran, Muhammad (Frontiers in Toxicology, 2025)
Plastics are globally considered a significant threat, particularly to metropolitan areas, due to the extensive use of plastic products. This research is the first of its kind to document microplastics contamination and its effects on Red wettled lapwing (Vanellus indicus). The concentration of microplastics (MPs) was measured from surface water at different locations including canals and drains, which are the primary sources of MPs pollution in the metropolitan city Lahore, Pakistan. The highest MPs concentration was recorded in the main stream of the Ravi River, with an average concentration of 5,150 ± 7.5 particles/m3. In addition, considering the different shapes of MPs, fibers were found to be most abundant at Site I (Main Stream of River Ravi), with the highest mean concentration of 92.4 ± 0.3 particles/m3, whereas the lowest mean concentration of 29.9 ± 0.1 particles/m3 was observed. In contrast, fragments were predominant at Site II (Shahdara Drain), with the highest and lowest mean concentrations of 42.6 ± 0.3 and 21.7 ± 0.1particles/m3, respectively. Chemical analysis revealed that most fragments, fibers; and beads belonged to the polyethylene class, while sheets were categorized as polypropylene and foam as polystyrene. The large MPs with particle size ranging from 400 μm to 5 mm were most abundant at both locations. Particles smaller than 0.5 mm were the most prevalent (56%) at Site I, while Site II showed the lowest proportions for size ranges 0.5–1 mm (24%), 1–2 mm (16%), 2–3 mm (8%), 3–4 mm (5%), and 4–5 mm (3%). The frequency of occurrence (%FO; prevalence) of plastics in necropsied birds was 89.7%. A total of 120 items were analyzed: 64 fibers, 23 fragments, 10 pieces of foam, 14 pieces of sheet, and 9 beads. Of the total ingested plastic debris analyzed, the largest proportion was comprised of polyethylene, making up 46% of the samples. Birds from Site I (Main Stream of River Ravi) had 100% of their organs containing plastic items compared to those from Site II (Shahdara Drain). Quantitative and qualitative histopathological analyses were performed to examine variations in prevalence percentage, frequency, and histological alteration indices (HAI) as a consequence of MPs exposure on the health of wild species. Tissue samples from the liver and kidneys of the Red-wattled lapwing were analyzed, and comparisons were made to assess the extent of damage and degree of alteration in bird organs. The study evaluated the impacts of ingested MPs, which induced inflammatory and anatomical responses in V. indicus. Significant tissue damage was observed, including considerable inflammatory responses, evident cellular swelling in many renal tubular epithelial cells, and pyknotic nuclei, which were major causes of necrosis and apoptosis. Prevalence percentage and frequency were significantly higher at Site I compared to Site II. The highest prevalence percentages in the liver and kidneys were 90% and 85%, respectively, manifesting as degeneration of hepatocytes and necrosis in renal tubular epithelial cells in response to 0.5–1 mm sized MPs. The lowest prevalence percentage, 5%, was observed as congestion of sinusoids and hyperemia in response to 4–5 mm sized MPs. The frequency and prevalence percentages followed the order: 0.5 mm > 0.5–1 mm > 1–2 mm > 2–3 mm > 3–4 mm > 4–5 mm > 0 mm (0 mm as control).This investigation contributes to the growing documentation of MPs abundance in freshwater ecosystems and provides a baseline for future studies on MPs pollution in the Ravi River.